Bamboonimics in Tegaren Village - Jojok Dwiridhotjahjono; Prihandono Wibowo; Praja Firdaus Nuryananda (Future Science)
Besek is made from bamboo which is then woven. This besek craft is the main craft of women in Tegaren Village. However, problems arise when besek does not provide enough income for women in Tegaren Village. By providing more training and insight for the residents of Tegaren Village, it is hoped that there will be an increase in the economic capacity of the village. The method of implementing the Community Partnership Program (PKM) is through comparative studies, training, as well as providing assistance to residents of Tegaren Village to continue to improve their economic capacity through bamboo woven commodities. As an object of comparative study, bamboo craft center Bamboo Indah was chosen, located in Wonoanti Village, Gandusari District, Trenggalek Regency. During a comparative study, three agreements were reached between the government of Tegaren Village and the Bambu Indah center, namely 1) Tegaren Village would send two or three craftsmen to conduct intensive bamboo weaving training, 2) two